Green fluorescent protein (GFP) tagged to the cytoplasmic tail of alphaIIb or beta3 allows the expression of a fully functional integrin alphaIIb(beta3): effect of beta3GFP on alphaIIb(beta3) ligand binding. - Plançon, S (2001)
Using green fluorescent protein (GFP) as an autofluorescent tag, we report the first successful visualization of a beta3 integrin in a living cell. GFP fused in frame to the cytoplasmic tail of either alphaIIb or beta3 allowed normal expression, heterodimerization, processing and surface exposure of alphaIIbGFPbeta3 and alphaIIb(beta3)GFP receptors in Chinese hamster ovary (CHO) cells. Direct microscopic observation of the autofluorescent cells in suspension following antibody-induced alphaIIb(beta3) capping revealed an intense autofluorescent cap corresponding to unlabelled immunoclustered GFP-tagged alphaIIb(beta3). GFP-tagged alphaIIbbeta3 receptors mediated fibrinogen-dependent cell adhesion, were readily detectable in focal adhesions of unstained living cells and triggered p125(FAK) tyrosine phosphorylation similar to wild-type alphaIIb(beta3) (where FAK corresponds to focal adhesion kinase). However, GFP tagged to beta3, but not to alphaIIb, induced spontaneous CHO cell aggregation in the presence of soluble fibrinogen, as well as binding of the fibrinogen mimetic monoclonal antibody PAC1 in the absence of alphaIIb(beta3) receptor activation. Time-lapse imaging of living transfectants revealed a characteristic redistribution of GFP-tagged alphaIIb(beta3) during the early stages of cell attachment and spreading, starting with alphaIIb(beta3) clustering at the rim of the cell contact area, that gradually overlapped with the boundary of the attached cell, and, with the onset of cell spreading, to a reorganization of alphaIIb(beta3) in focal adhesions. Taken together, our results demonstrate that (1) fusion of GFP to the cytoplasmic tail of either alphaIIb or beta3 integrin subunits allows normal cell surface expression of a functional receptor, and (2) structural modification of the beta3 integrin cytoplasmic tail, rather than the alphaIIb subunit, plays a major role in alphaIIb(beta3) affinity modulation. With the successful direct visualization of functional alphaIIb(beta3) receptors in living cells, the generation of autofluorescent integrins in transgenic animals will become possible, allowing new approaches to study the dynamics of integrin functions.